Calcium Channel Blocker Overdose Simulation - Michael Maniaci; Delaney La Rosa; Leslie Simon (Association of American Medical Colleges, 2015)
Abstract Introduction Accidental poisoning and drug overdose are a common occurrence in the emergency medicine setting. Often it is unknown what substances the patient has taken. This high-fidelity simulation focuses on developing a physician's clinical exam and clinical reasoning skills. By using the evidence given in the simulation, the physician can deduce that this is a poisoning of a cardiotoxic medication and once discovering the source, their medical knowledge skills are put to the test to treat the underlying condition and all the complications. This high-fidelity simulation scenario is appropriate for emergency medicine residents, internal medicine/family medicine residents, and third-/fourth-year medical students doing an emergency medicine rotation. Methods This scenario utilized a standardized patient who presented with somnolence and delirium with the presumed diagnosis of opioid overdose. It is only after thorough clinical examination and EKG review that the learner discovers the patient's symptoms are likely caused by a calcium channel blocker overdose. This case includes several branches from least complex to most complex and may progress, at the discretion of the instructor, up to the point of a full code. In addition to details required for setting up and managing the scenario and branches, this resource also includes robust debriefing materials. Results This scenario was used successfully seven times over the past year with 21 participants. All levels of residents are able to figure out the underlying diagnosis, but only the advance level learners (PGY2-PGY3) were able to come up with the advanced treatments. Discussion Through this simulation, the realism of a clinical toxicology case is set into motion so the direct effect of medical decisions on the patient's outcome can be seen in real time, but without real consequence. This is an important educational experience for learners who will be in a real setting in the future. A clinical educator can use this simulation to test a number of learners at various levels of education (i.e., student, intern, resident, fellow), but the ideal number is one to three.